Offering Organizational Legitimacy: Foreign Underwriters and Outside Directors in Philippine IPOs - Lizares, Regina M (Philippine Management Review, 2023)
This study explores the organizational legitimacy offered by underwriters and outside directors on firms going public. Informed by legitimacy theory, certification hypothesis, and resource dependence theory, this study investigates the association of underwriters and outside directors on the level of underpricing. Using a sample of 77 Philippine firms undertaking an initial public offering (IPO) for the 20-year period from 2001 to 2020 and cross- sectional multiple regression, results indicate that the presence of a foreign underwriter and a greater proportion of outside directors on the board reduces the level of underpricing. Their legitimizing presence allows listing firms to potentially maximize their IPO proceeds.